Head and neck surgery is a risk factor for atrial fibrillation: incidence and outcomes. Issue 12 (December 2020) - Weyh, A.M.; Esmail, K.; Yekikian, M.; Catanzaro, J.N.; Bunnell, A.M.; Elayi, C.S.; Fernandes, R.P.
Abstract: Atrial fibrillation (AF) is the most common postoperative arrhythmia and can cause increased length of stay, costs, morbidity, and mortality. Little information exists about postoperative AF after major head and neck surgery, but it is thought to occur more frequently than after surgery at other extra-thoracic sites. A retrospective cohort study was implemented, including patients who had undergone major head and neck surgery and who had follow-up records covering a minimum of 60 days postoperative. The main outcome was the incidence of new onset postoperative AF after major head and neck surgery; secondary outcomes were the incidence of any AF, the role of cardiology, predictors of AF postoperatively, and clinical outcomes. A total 337 patients were included. Twenty-four patients experienced AF postoperatively (7.1%), of whom 12 (3.6%) had new onset AF. New onset AF was associated with advanced age of ≥65 years (odds ratio 11.6, P = 0.027) and having a laryngectomy (odds ratio 9.9, P = 0.003). Postoperative AF following major head and neck surgery is not a rare phenomenon and can be associated with considerable morbidity and costs due to the need for intensive care, specialty consultations, additional testing and laboratory studies, and cardiology follow-up.